Does The Conventional Performance Measurement Of Sharia Bank Need To Be Reviewed:A Critical Thought - Satia Nur Maharani; Setya Ayu Rahmawati; Syihhabudin Syihhabudin (Journal of International Conference Proceedings (JICP), 2019)
There is some evidence of a successful Islamic business pattern. One of the centers of attention is syariah banks. As one of the patterns of Islamic business that has very rapid development both in Muslim-majority and non-Muslim countries, there is one important issue that needs to be addressed immediately, namely performance measurement. The performance measurement model that has been implemented so far uses conventional models such as CAMEL and RGEC. Recent research shows how the model is not able to measure the social aspects and da’wah inherent in Islamic banks. Financial aspects become an important focus so that the operational orientation of Islamic banks is only for the achievement of financial aspects. In the end, several studies found dysfunctional behaviors in Islamic banks. One of the dysfunctional behaviors is ignoring the provision of productive funding to small entrepreneurs. This article presents critical thought method related to the performance measurement of Islamic Banks in terms of several perspectives, both legal, sociocultural and expected measurement models.